Transforming Educational Leadership: Digital Applications of Ki Hajar Dewantara’s Leadership Principles - Welius Purbonuswanto; Sutama Sutama; Didi Supriadi; Mazlini Binti Adnan; Mohamad Waluyo (Universitas Muhammadiyah Surakarta, 2024)
In the face of rapid technological developments, digital leadership in the leadership of Ki Hadjar Dewantara plays an important role in ensuring that digital technology is used effectively and efficiently for educational goals. The research aims to develop a model of digital integration of leadership in the leadership trilogy of Ki Hadjar Dewantara at Tamansiswa College. The research used a quantitative approach with survey methods. The sampling technique used purposive sampling with a total sample of 116 people. The data collection technique in this research used a questionnaire using a five-option Likert. The data analysis technique is the Structural Equation Model (SEM) using SmartPLS version 3 software. The leadership trilogy by Ki Hajar Dewantara is highly suitable for school principals to implement in their digital leadership practices for principals and teachers. The concept of Ing ngarso sung tuladha is particularly relevant to modern digital leadership. Implementing Ing ngarso sang tuladha in the digital domain, leaders may motivate their people, establish trust, and successfully traverse the intricacies of the digital era. The school principal can implement the Ing madya mangun karsa concept in a digital context. The school principal encourages collaboration and co-creation, recognizing the immense potential for collaborative work in digital domains. The Tut wuri handayani approach encourages digital leaders to cultivate a culture of autonomous learning, empowering team members to actively pursue knowledge, acquire new abilities, and adjust to the evolving digital environment.